Systematic Exposition to The Consequential Implications of Procreation Under the Qur’an and Hadith: Eksposisi Sistematis Terhadap Implikasi Konsekuensial Dari Prokreasi Menurut Al-Quran Dan Hadis - Ahmed Abiodun Muhammed-Mikaaeel; Anifat Tosin Salaudeen (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
Background and Objectives: The recurring global economic recession has exacerbated financial challenges, particularly among Muslim families practicing uncontrollable procreation without considering their economic means. This study aims to examine the implications of procreation through the lens of Shari‘ah, emphasizing the correct understanding of Qur’anic and Prophetic guidance on the topic. It seeks to highlight the balance between religious encouragement for procreation and the financial and spiritual responsibilities mandated by Islamic law. Methodology: Employing a doctrinal methodology, the research relies on primary sources—the Qur’an and Hadith—supplemented by secondary materials, including the opinions of classical and contemporary Islamic scholars. Content analysis is used to derive and analyze the relevant principles from these sources. The main results: The study finds that misinterpretations of certain Qur’anic verses (e.g., Chapter 17:31) and Prophetic Hadith on procreation have led to practices of unchecked procreation, compounding financial difficulties for many families. This research contribution: a new dimension by framing procreation within the context of maqasid al-Shari‘ah (objectives of Islamic law), advocating a preventive approach that integrates religious obligations with socio-economic realities. Conclusion: the dual religious and financial responsibilities of parents, as mandated by the Qur’an and Hadith, emphasizing that procreation should be undertaken responsibly to avoid poverty and societal burdens